Path dependence and human rights improvement. Issue 1 (1st January 2020) - Cingranelli, David; Filippov, Mikhail
Abstract: Though nearly all countries of the world have promised to respect human rights, there are two groups of countries in the world: one where human rights are improving and another where they are not. Countries in the improving human rights group also are improving in many other ways. The logic of institutional "path dependence" explains why only a minority of countries are in the improving group and why it is difficult to switch from a bad trajectory to a good one. It emphasizes that new formal rules including human rights often fail to constrain political and economic actors. Further exploration of these ideas requires a new research agenda focusing less on year-to-year changes and more on long-term trends. It also should concentrate less on assessing the impact of one formal institution at a time and more on identifying the full range of supporting institutional arrangements necessary for improving human rights.